Real‐Time Nitrification Control Nets Energy Savings. Issue 7 (1st July 2016) - Lunn, Mike; Dabkowski, Bob; Morgan, Laron; Craig, Kathryn; Ingleright, John
Abstract : The city of Grand Rapids, Mich., installed a real‐time nitrification control system to reduce the energy consumed by its wastewater treatment facility's aeration process.